ANALISIS KESULITAN BELAJAR PERKALIAN DI KELAS II SEKOLAH DASAR - diyah, halimatussa; Maryono, Maryono; Pamela, Issaura Sherly (Jurnal Tunas Pendidikan, 2025)
This research aims to describe students' analysis of learning difficulties in class II multiplication material at SD Negeri 13/1 Muara Bulian. The methodology used in this research is a qualitative method with the type of research being a descriptive case study. This selection approach considers that the cases under study require observation and there will also be closeness between researchers and respondents so that it will produce in-depth data. The researcher chose the type of descriptive case study research because this type of research accurately describes the problems that existed when the researcher conducted the research (currently) or an actual problem, and is based on the facts of the problem being researched so that he can find out about the difficulties of analyzing student learning at school. student bases obtained from observations and interviews sourced from class II students and teachers at SD Negeri 13\1 Muara Bulian, as well as documentation in the form of photos and sound recordings which can be used as support for data collection. This observation was carried out for about three days. Next, students are given a questionnaire, which first accounting them on how to fill it out. The results of the instrument used to detect student learning difficulties are explained using the application by looking at the profile graph. At Piaget's cognitive stage, the characteristics of grade II elementary school students have the ability to think concretely, so that elementary school students will absorb the material more if the material can be seen in real life and experience learning. This research uses the Polya procedure, which is divided into 4 stages, namely; understand the problem, solve the problem, and review the completeness of the problem solution. helping the average second grade student at SD Negeri 13/1 Muara Bulian at the stage of understanding the problem was 95.5%. The average completion at the problem solving planning stage is 97.7%. And the average difficulty at the stage of reviewing the completeness of problem solving is 79.5%. Factors causing difficulties for class II students in solving mathematical problems in multiplication material based on the Polya procedure include intellectual factors, padagogy. facilities and environment. The implication of this research is that the results of this research are expected to increase teachers' insight into the difficulties of learning multiplication in class II, apart from that this research can also be a reference source for Jain researchers who research the same topic.